A study on challenges distribution zakat to asnaf during Covid 19 in Selangor - Irnawati Zainal; Maisarah Zakariah; Ku Mohammad Ku Hashim; Kamaruddin Alpi; Noormariana Mohd Din (2022)
The Covid-19 outbreak has shifted everyone's priorities. This has put pressure on the global health industry, which has impacted the global economy. The purpose of this study is to look at the issues that Selangor zakat beneficiaries encounter in the COVID-19 situation in Selangor. This is a qualitative research project. Three impoverished zakat beneficiaries practitioners provided data via questionnaires and interviews, which were performed via online interviews and phone conversations. Atlas.ti was used to create the themes. For example, expertise, service quality, and incentives for zakat delivery to asnaf.